On the consequences of natural-grammatical gender conflicts. The case of Myszka Miki - Manasterska-Wiącek, Edyta (Papers in Linguistics, 2025)
The conflict between grammatical gender and natural (referential) gender in the Polish language often results in difficulties combining words burdened with such a feature with dependent items. The aim of the article is to discuss the negative consequences of rendering Mickey Mouse, the name of a famous American children’s film male character, into Polish as Myszka Miki. The author reports on two empirical studies she conducted employing different methodologies (Study 1, a survey carried out among schoolchildren; Study 2, based on texts written by adults). The studies demonstrate the problem of aligning linguistic elements to achieve gender concord, with structures sometimes adapted to natural gender and in other cases to grammatical gender (e.g. mała Myszka Miki poszła ‘the little (feminine) Mickey (masculine) Mouse (feminine) went (feminine),’ mały Myszka Miki poszedł ‘the little (masc.) Mickey (masc.) Mouse (fem.) went (masc.)’). Both studies show that the use of the Polonized name Myszka Miki brings about negative effects in texts written by both children and adults. They include grammatically deviant and absurd combinations of words, resulting in unintended and undesirable humorous effects, hindered reception of cultural texts, and dilemmas in choosing dependent gender forms. Additionally, the author points out the consequences of translators’ decisions to transfer character names which are inconsistent with natural gender.